The Impact of an Educational Intervention on Neonatal Care and Survival. Issue 2 (April 2023) - Emmanuel, Andy; Kain, Victoria J.; Forster, Elizabeth
Abstract : Objective: Under-5 mortality has declined globally; however, proportion of under-5 deaths occurring within the first 28 days after birth has increased significantly. This study aims to determine the impact of an educational intervention on neonatal care and survival rates in Nigeria. Methods: This was a sequential exploratory mixed-methods design involving 21 health workers in the preintervention phase, while 15 health workers and 30 mother-baby dyads participated in the postintervention phase. Data were collected using semistructured interviews and nonparticipatory observation. Qualitative data were analyzed using thematic analysis, while quantitative data were analyzed using descriptive and inferential statistics. Results: Healthy newborns were routinely separated from their mothers in the preintervention period. During this time, non-evidence-based practices, such as routine nasal and oral suctioning, were performed. Skin-to-skin contact and early initiation of breastfeeding were frequently interrupted. After the intervention, 80.6% were placed in skin-to-skin contact with their mothers, and 20 of these babies maintained contact with the mother until breastfeeding was established. There was decline in neonatal deaths post-intervention. Independent t -test analysis of the day of neonatal death demonstrates a significant difference in mean ( P = .00, 95% confidence interval −5.629; −7.447 to −4.779). Conclusion: Newborn survival can be improved through regular training of maternity health workers in evidence-based newborn care.